(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The paper analyzes the fierce moralist William Wycherley’s perspective on the mistreatment of women by the Restoration era’s aristocratic class. To get there, Wycherley divides the characters in The Country Wife into four camps: the abuser, the victim, the self-made victim, and the role model. The first category consists of rakes like Horner and company, the second of Margery and other good ladies, the third of self-made cuckolds like Pinch wife and Sir Jasper Fidget, and the fourth of Wycherley’s mouthpieces like Alithea and Harcourt. The dramatist sees parallels between these two sorts in the female characters’ flaws. In contrast, Wycherley shows extraordinary compassion for all female victims. Margery is portrayed as a helpless victim of her obsessive and overprotective husband and of the corrupt culture in which they live. This also applies to the lovely girls out there. They were entirely ignored by their husbands, leading them to adultery and extramarital affairs. Despite his compassion for the victims, Wycherley supports exemplary characters’ behavior over the victims’ flirtation.